The Role of Technology and Social Media in Spreading the Qur'an and Hadiths by Mubalig - Hidayaturrahman, Mohammad; Putra, D.I Ansusa (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This research was conducted to find out how the role of technology and social media in spreading Al-Quran and hadith by the mubalig. This research used qualitative descriptive approach, while the method of collecting the data was observation on the activities of the mubalig and dai who perform religious da’wa activities, both in mosques, langgar, and majlis taklim assemblies held at homes of pilgrims or mubalig house. This research found that, mubalig already using technology and social media for the purposes of their da’wa. The preachers use technology and social media for various purposes of da’wa, communicating with the congregation of recitation, to read references of religious material, as well as as a means to store the propagation material which subsequently submitted during the recitation. The last is to make use of the existing apps in their devices to recall verses or hadiths that happen to be forgotten when delivering lecture materials. The mubalig rate, technology and social media are something positive to use as a medium of preaching communication. Thus, mubalig are not allergic to technology and social media, even some of them become active users in social media. Similarly, in his own devices, there are many applications of the Qur’an and Hadith. Carrying a device is an effective way of learning, carrying the reference of the book, because mubaligh does not have to bring a physically large book when doing preachings to various places and locations. Technology is considered to be able to connect them with the other ustaz, kiai or religious figures in the same or different organizations.